Competitiveness and Innovation - Viteri Moya, Jorge (2011)
Competitiveness is the ability of organizations to respond to the needs that the market presents, in search of delivering greater benefits and positioning itself as a leader in the competitive business world. It is there where innovation enters, as a process that is part of the technological, artistic, scientific, philosophical or organizational culture, and that becomes the engine of competitiveness. In Ecuador, the road to match both concepts in practice is still long and requires the implementation of both state policies that facilitate entrepreneurship, as well as the work of companies to generate innovative ideas that generate tangible and economically viable benefits.